System Productivity and Resource Use Efficiency of Alternative Cropping Systems for Sugarcane in Karnataka - Sadashivanagowda, S. N. O.; Alagundagi, S. C.; Nadagouda, B. T.; Bidari, B. I.; Chimmad, V. P. (International Journal of Bio-resource and Stress Management, 2021)
The field experiments were conducted at Agricultural Research Station, Hukkeri, Belagavi, Karnataka, India during 2018–19 and 2019–20 to study the system productivity and resource use efficiency of alternative cropping systems for sugarcane. There were 11 treatments involving different cropping systems viz., soybean–sorghum–ridge gourd, pigeon pea±green gram (1:1)–beans, pigeon pea±soybean (1:1)–cowpea, soybean–wheat–groundnut, groundnut–sorghum–sesame, maize–cabbage–fallow, soybean–wheat–green gram, maize–wheat–sesame, Bt cotton–groundnut, sugarcane±onion (1:2) and sugarcane (sole) replicated thrice and laid out in randomized complete block design. Among the cropping systems, maize-cabbage-fallow system recorded significantly higher total system productivity (58,234 kg ha-1), water use efficiency (199.67 kgha-1-mm) and energy use efficiency (129.91 MJha-1) compared to rest of the cropping systems. However, sugarcane (sole) recorded (1,11,008 kg ha-1, 68.64 kg ha-1-mm and 16.58 MJ ha-1, respectively). Based on alternative cropping systems involving only field crops, maize-wheat-sesame (9633 kg ha-1, 30.65 kg ha-1-mm and 132.20 MJ ha-1,respectively), soybean-wheat-groundnut (7602 kg ha-1, 27.40 kg ha-1-mm and 32.35 MJ ha-1,, respectively), soybean-wheat-green gram (6424 kg ha-1, 23.05 kg ha-1-mm and 31.91 MJ ha-1, respectively) and Bt cotton-groundnut (4503 kg ha-1,17.97 kg ha-1-mm and 16.95 MJ ha-1,, respectively) were significantly higher. By adopting the alternative cropping systems, there was water saving of approximately 45% compared to sugarcane monocropping and sugarcane±onion (1:2) intercropping.